2011
DOI: 10.1152/ajprenal.00518.2010
|View full text |Cite
|
Sign up to set email alerts
|

WNK4 kinase inhibits Maxi K channel activity by a kinase-dependent mechanism

Abstract: [with no lysine (k)] kinase is a serine/threonine kinase subfamily. Mutations in two of the WNK kinases result in pseudohypoaldosteronism type II (PHA II) characterized by hypertension, hyperkalemia, and metabolic acidosis. Recent studies showed that both WNK1 and WNK4 inhibit ROMK activity. However, little is known about the effect of WNK kinases on Maxi K, a large-conductance Ca 2ϩ and voltage-activated potassium (K) channel. Here, we report that WNK4 wild-type (WT) significantly inhibits Maxi K channel acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 63 publications
(65 reference statements)
6
55
0
Order By: Relevance
“…This finding suggests that WNK1 activates BK channel activity by reducing its degradation through a lysosomal pathway, likely by inhibiting an ERK1/2 signaling pathway, a mechanism similar to WNK4-mediated modulation of BK but in the opposite direction. 7,8 WNK1 was found to inhibit ROMK activity and its protein expression and KS-WNK1 reversed wild-type (WT)-WNK1's inhibitory effects on ROMK. 6,45 Several studies have shown that the ratio of WT-WNK1 to KS-WNK1 is relevant to K secretion.…”
Section: Hek Bka Cells Were Transfected With a Series Of Doses Of Wnkmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding suggests that WNK1 activates BK channel activity by reducing its degradation through a lysosomal pathway, likely by inhibiting an ERK1/2 signaling pathway, a mechanism similar to WNK4-mediated modulation of BK but in the opposite direction. 7,8 WNK1 was found to inhibit ROMK activity and its protein expression and KS-WNK1 reversed wild-type (WT)-WNK1's inhibitory effects on ROMK. 6,45 Several studies have shown that the ratio of WT-WNK1 to KS-WNK1 is relevant to K secretion.…”
Section: Hek Bka Cells Were Transfected With a Series Of Doses Of Wnkmentioning
confidence: 99%
“…HEK293 cells stably expressing the a subunit of BK (HEK BKa cells) were previously generated in our laboratory and maintained in DMEM supplemented with penicillin (100 U/ml), streptomycin (100 U/ml), G418 200 mg/10 ml, and 10% FBS. 7 Lipofectamine 2000 (Life Technologies) was used for transfection according to the manufacturer's instructions. Forty-eight hours after transfection of cells with a series of doses of WNK1 plasmid, cells were lysed.…”
Section: Plasmids and Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…These channels, which are less abundant in principal cells, are activated by depolarization, stretch/luminal flow, intracellular calcium increases, or hypoosmotic stress (reviewed in reference 67). Moreover, the BK channel is inhibited by the with-no-lysine kinase 4 (WNK4) in a phosphorylationdependent manner (68,69). In a later study performed in a cell line of intercalated cell characteristics, WNK4 inhibited BK channel activity in part by increasing channel ubiquitination and degradation (70).…”
Section: Type a Intercalated Cells Their Major Transport Proteins Amentioning
confidence: 99%